A Case Report on Group “G” B-Hemolytic Streptococcus, a New Important Causative Organism of Localised Intra-Abdominal Abscess - Shiv Chopra; V. K. Aneja; Raman Sardana; Leena Mehndiratta (New Frontiers in Medicine and Medical Research Vol. 4, 2021)
Group “G” Streptococcus is an ubiquitous non-pathogenic commensal organism found in the skin, throat, gut, appendix and the female genital tract. As per our review of the available literature we present the first reported case of localized intra-abdominal abscess caused by Group g streptoccoccus (GGS) also seen first time in our institution which is a rare but an important cause when after the requisite Surgical procedure-drainage and antibiotic regimens the post-operative pyrexia/symptoms do not settle down with rising counts then one should start thinking about upgrading the antibiotics to meropenem+ciprofloxacin/vancomycin/teichoplanin along-with the existing anaerobic cover. In our case blood cultures were negative, only the pus culture-liquid subcultures grew large colony gram positive cocci on the 1st postoperative day with further identification as Group G Streptococcus (GGS) with the sensitivity pattern on the 3rd postoperative day identified the organism as large-so a very good microbiology department team is necessary which in our case was instrumental in the management of our patient with a very high index of suspicion. This case is being reported for the reason of its rarity. Especially reported in patients who are diabetics/ malignancies/respiratory infections/immunosuppressed/chronic leg ulcers/pet dogs at home it is gaining importance as an organism for causing deep-seated abscesses in the body especially the abdomen which are usually multiple or as peritonitis. Another important reason mentioned in literature for immediate and urgent drainage of abscess caused by GGS infections is that this may lead to a very serious streptococcal toxic shock syndrome having a very fulminant and rapid downhill course with GGS bacteremia having a high 30 days mortality rate of to 15%.